Ang-(1-7) protege fatias de hipocampo do cérebro de camundongos contra o dano isquêmico modulando o tráfego de receptores de glutamato do tipo AMPA - Gabriela Maria de Abreu Gomes (2016)
Stroke is caused by a decrease in blood flow, which leads to a complete absence of oxygen (anoxia) and low oxygen (hypoxia) together with the absence or low glucose delivery and this event by itself is an event that causes damage (ischemia). Cerebral ischemia results in a cascade of metabolic events that cause important deleterious cellular changes. After ischemic insult neurons may die immediately after injury or until 10 days later. This is due to metabolic alterations, such as rapid decrease of ATP, loss of membrane integrity, release of Ca2+ from intracellular stores, increased Ca2+ permeability, loss of ionic homeostasis, excitotoxicity, enzyme activation and mitochondrial dysfunction. The loss of ion homeostasis during ischemic process leads to excessive glutamate release, causing glutamatergic excitotoxicity, and finally neuronal death. Expression of glutamatergic AMPA receptor is modified by ischemic process. Under physiological conditions there are AMPARs GluR2-containing, which makes the channel impermeable to divalent ions such as Ca2 + and Zn2 +.During the ischemic process occurs internalization and subsequent degradation of GluR2, increasing the channel permeability to Ca2+.Although it was discovered more than 100 years ago, the renin angiotensin system further has a key role in treating various cardiovascular diseases. All components shaft ACE2 / Ang- (1-7) / ACE are expressed in brain tissue and play a crucial role in neuroprotection in cases of ischemia. Several studies suggest that the administration Ang-(1-7) reduces infarct area and produces brain protection in stroke models in rodents, but the mechanisms by which Ang- (1-7) promotes neuroprotection are not yet fully elucidated. The aim of this study was to investigate whether Ang- (1-7) promotes neuroprotection by modulating AMPA glutamate receptors .In order to develop this work, hippocampal slices were subjected to OGD protocol, divided into groups tests and controls with Ang- (1-7) and receptor antagonist Mas ,A-779, to evaluate cell viability, AMPA receptor subunit expression, GluR2 and GluR1 total and membrane expression and also glutamate released. Our results show that Ang- (1-7) was able to reduce cell death in hippocampal slices subjected to in vitro ischemia. As a possible protective mechanism, we found that treatment with Ang- (1-7) prevented the internalization and degradation of the GluR2 subunit of the AMPA receptor. In addition, our work also showed that treatment with Ang- (1-7) reduced glutamate release and reduced cell death stimulated by AMPA agonist.